Partnering for peace : Australia's peacekeeping and peacebuilding experiences in the Autonomous Region of Bougainville in Papua New Guinea, and in Solomon Islands and Timor-Leste - Australian Civil-Military Centre ([Canberra, ACT] : Australian Civil-Military Centre, 2012)
"This report seeks to capture the experiences, innovations and practical lessons that have emerged over the last two decades from Australia's contributions to peace operations in support of our regional neighbours-Papua New Guinea's Autonomous Region of Bougainville, Solomon Islands and Timor-Leste. The analysis of peace operations in these three countries highlights the strength of partnerships between the operations and the local leadership, and underlines the core principle that in order to have a sustainable impact, peace operations must be aligned with local priorities and support local capacities."--Foreword.
Caption title.
"Published 2012"--Cover verso.
Includes bibliographical references.
Also available online. Address as at 02.06.2019
Keywords: Integrated operations (Military science); Military assistance, Australian; Nation-building -- Papua New Guinea -- Bougainville Island; Nation-building -- Timor-Leste.; Nation-building -- Solomon Islands; Australian